Fiber-Optic Sensor for Detecting PFAS Compounds in Water Using a Fabry–Pérot cavity - Radek, Patryk; Barczak, Kamil; Olszewska, Aneta (Photonics Letters of Poland, 2025)
A PVDF‐coated Fabry–Pérot fiber‐optic sensor was developed for rapid in situ detection of PFAS in water. A low‐finesse etalon was formed by dip‐coating, yielding interference minima that shift by an average of 5 nm during wet–dry cycling (SD = 0.7 nm). Exposure to a 10 µg/mL PFOS solution induced a reversible 5.9 nm redshift, and subsequent rinsing restored the baseline within 0.4 nm. The sensor’s low cost, portability, and high repeatability make it well suited for field applications. Full Text: PDF References Carbon-Fluorine Bond Strength, Alfa Chemistry Fluoropolymers Resource, DirectLink Z. Abunada, S. Safi, A. Ahmad, M.M.F. Chitta, "An Overview of Per- and Polyfluoroalkyl Substances (PFAS) in the Environment: Source, Fate, Risk and Regulations", Water 12(12), 3590 (2020), CrossRef C.F. Kwiatkowski, M.L. Cannon, D.T. Hoffman, J.A. Buck, S.A. Fedorak, "Scientific Basis for Managing PFAS as a Chemical Class", Environ. Sci. Technol. Lett. 7(8), 532 (2020). CrossRef P. Radek, K. Barczak, A. Olszewska, Optical fiber sensor for per- and polyfluoroalkyl substances (PFAS) in Proc. Integrated Optics - Sensors, Sensing Structures and Methods, IOS'2025, Szczyrk, Poland, Feb. 24-28, 2025, p. 81. <a class="file" href="https://omega.polsl.pl/info/article/PSL3998403963bc4062bddaa0febd4120c4?r=publication&ps=20&tab=&title=Publication%2B%25E2%2580%2593%2BOptical%2Bfiber%2Bsensor%2Bfor%2Bper-%2Band%2Bpolyfluotoalkyl%2Bsubstances%2B%2528PFAS%2B%25E2%2580%2593%2BSilesian%2BUniversity%2Bof%2BTechnology&lang=en" target="_parent"> DirectLink F. Faiz, S.J. Mihailov, D. Thapa, V. Kayunkid, G. Viney, "Polyvinylidene fluoride coated optical fibre for detecting perfluorinated chemicals", Sens. Actuators B Chem. 312, 128006 (2020). CrossRef